Upside Down

Algebra Level 3

Given that a , b a,b and c c are non-zero numbers satisfying 1 a + 1 b + 1 c = 0 \dfrac 1a + \dfrac 1b + \dfrac1c = 0 , calculate

b c a 2 + a c b 2 + a b c 2 . \dfrac{bc}{a^{2}} + \dfrac{ac}{b^{2}} + \dfrac{ab}{c^{2}}.


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

6 solutions

展豪 張
May 2, 2016

1 a + 1 b + 1 c = 0 \dfrac 1a+\dfrac 1b+\dfrac 1c=0
( a + b + c ) ( 1 a + 1 b + 1 c ) = 0 (a+b+c)(\dfrac 1a+\dfrac 1b+\dfrac 1c)=0
a b + b a + a c + c a + b c + c b = 3 ( 1 ) \dfrac ab+\dfrac ba+\dfrac ac+\dfrac ca+\dfrac bc+\dfrac cb=-3 \cdots (1)
1 a + 1 b + 1 c = 0 \dfrac 1a+\dfrac 1b+\dfrac 1c=0
1 a = 1 b 1 c ( 2 ) \dfrac 1a=-\dfrac 1b-\dfrac 1c \cdots (2)
b c a 2 + a c b 2 + a b c 2 \dfrac{bc}{a^2}+\dfrac{ac}{b^2}+\dfrac{ab}{c^2}
= ( 1 b 1 c ) 2 ( b c ) + ( 1 a 1 c ) 2 ( a c ) + ( 1 a 1 b ) 2 ( a b ) ) from ( 2 ) =(-\dfrac 1b-\dfrac 1c)^2(bc)+(-\dfrac 1a-\dfrac 1c)^2(ac)+(-\dfrac 1a-\dfrac 1b)^2(ab)) \text{ from }(2)
= 6 + a b + b a + a c + c a + b c + c b =6+\dfrac ab+\dfrac ba+\dfrac ac+\dfrac ca+\dfrac bc+\dfrac cb
= 6 3 from ( 1 ) =6-3 \text{ from }(1)
= 3 =3


Pham Khanh
May 3, 2016

1 a + 1 b + 1 c = 0 1 c = ( 1 a + 1 b ) \frac{1}{a}+\frac{1}{b}+\frac{1}{c}=0 \iff \frac{1}{c}=-(\frac{1}{a}+\frac{1}{b}) 1 c 3 = ( 1 a + 1 b ) 3 \iff \frac{1}{c^{3}}=-(\frac{1}{a}+\frac{1}{b})^{3} 1 c 3 = ( 1 a 3 + 3 a 2 b + 3 a b 2 + 1 b 3 ) = 1 a 3 1 b 3 ( 3 a 2 b + 3 a b 2 ) ( ) \iff \frac{1}{c^{3}}=-(\frac{1}{a^{3}}+\frac{3}{a^{2}b}+\frac{3}{ab^{2}}+\frac{1}{b^{3}})=-\frac{1}{a^{3}}-\frac{1}{b^{3}}-(\frac{3}{a^{2}b}+\frac{3}{ab^{2}}) \qquad (*) On the other hand, 3 a 2 b + 3 a b 2 \frac{3}{a^{2}b}+\frac{3}{ab^{2}} = 1 a × 3 a b + 1 b × 3 a b =\frac{1}{a} \times \frac{3}{ab}+\frac{1}{b} \times \frac{3}{ab} = 3 a b ( 1 a + 1 b ) =\frac{3}{ab}(\frac{1}{a}+\frac{1}{b}) = 3 a b × 1 c =\frac{3}{ab} \times -\frac{1}{c} = 3 a b c =-\frac{3}{abc} ( ) 1 c 3 = 1 a 3 1 b 3 + 3 a b c (*) \quad \iff \quad \frac{1}{c^{3}}=-\frac{1}{a^{3}}-\frac{1}{b^{3}}+\frac{3}{abc} 1 a 3 + 1 b 3 + 1 c 3 = 3 a b c \iff \frac{1}{a^{3}}+\frac{1}{b^{3}}+\frac{1}{c^{3}}=\frac{3}{abc} So b c a 2 + a c b 2 + a b c 2 \frac{bc}{a^{2}} + \frac{ac}{b^{2}} + \frac{ab}{c^{2}} = a × b c a × a 2 + b × a c b × b 2 + c × a b c × c 2 =\frac{a \times bc}{a \times a^{2}}+\frac{b \times ac}{b \times b^{2}}+\frac{c \times ab}{c \times c^{2}} = a b c a 3 + a b c b 3 + a b c c 3 =\frac{abc}{a^{3}}+\frac{abc}{b^{3}}+\frac{abc}{c^{3}} = a b c ( 1 a + 1 b + 1 c ) =abc(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}) = a b c × 3 a b c =abc \times \frac{3}{abc} = 3 =\Large \boxed{3}

Hung Woei Neoh
May 5, 2016

b c a 2 + a c b 2 + a b c 2 \dfrac{bc}{a^2} + \dfrac{ac}{b^2} + \dfrac{ab}{c^2}

We know that:

1 a + 1 b + 1 c = 0 b c + a c + a b a b c = 0 a b + a c + b c = 0 \dfrac{1}{a} + \dfrac{1}{b} + \dfrac{1}{c} = 0\\ \dfrac{bc+ac+ab}{abc}=0\\ ab+ac+bc=0

This implies that:

b c = a b a c a c = a b b c a b = a c b c bc=-ab-ac \quad ac=-ab-bc \quad ab=-ac-bc

Substitute these in:

b c a 2 + a c b 2 + a b c 2 = a b a c a 2 + a b b c b 2 + a c b c c 2 = ( b + c a + a + c b + a + b c ) = ( b c ( b + c ) + a c ( a + c ) + a b ( a + b ) a b c ) = ( b 2 c + b c 2 + a 2 c + a c 2 + a 2 b + a b 2 a b c ) = ( a 2 b + a 2 c + a b 2 + b 2 c + b c 2 + a c 2 a b c ) = ( a ( a b + a c ) + b ( a b + b c ) + c ( b c + a c ) a b c ) \dfrac{bc}{a^2} + \dfrac{ac}{b^2} + \dfrac{ab}{c^2}\\ =\dfrac{-ab-ac}{a^2} + \dfrac{-ab-bc}{b^2} + \dfrac{-ac-bc}{c^2}\\ =-\left( \dfrac{b+c}{a} + \dfrac{a+c}{b} + \dfrac{a+b}{c} \right)\\ =-\left( \dfrac{bc(b+c) + ac(a+c) + ab(a+b)}{abc} \right)\\ =-\left( \dfrac{b^2c + bc^2 + a^2c + ac^2 + a^2b + ab^2}{abc} \right)\\ =-\left( \dfrac{a^2b + a^2c + ab^2 + b^2c + bc^2 + ac^2}{abc} \right)\\ =-\left( \dfrac{a(ab + ac) + b(ab + bc) + c(bc + ac)}{abc} \right)

Again, from the equation a b + a c + b c = 0 ab+ac+bc=0 , we know that:

a b + a c = b c a b + b c = a c a c + b c = a b ab+ac=-bc \quad ab+bc=-ac \quad ac+bc=-ab

Substitute again:

( a ( a b + a c ) + b ( a b + b c ) + c ( b c + a c ) a b c ) = ( a ( b c ) + b ( a c ) + c ( a b ) a b c ) = 3 a b c a b c = 3 -\left( \dfrac{a(ab + ac) + b(ab + bc) + c(bc + ac)}{abc} \right)\\ =-\left( \dfrac{a(-bc) + b(-ac) + c(-ab)}{abc} \right)\\ =\dfrac{3abc}{abc}\\ =\boxed{3}

Nihar Mahajan
May 3, 2016

Substitute ( a , b , c ) = ( 1 , ω , ω 2 ) (a,b,c)=(1,\omega,\omega^2) where ω \omega denotes complex cube root of unity and then using ω 3 = 1 \omega^3=1 the expression simplifies to 3 \boxed{3} .

Moderator note:

Ideally, a solution should present the general case, instead of a specific scenario.

Hải Trung Lê
May 3, 2016

There are 2 ways to prove this: 1. We will use a 3 + b 3 + c 3 3 a b c = ( a + b + c ) ( a 2 + b 2 + c 2 a b b c c a ) a^{3} + b^{3} + c^{3} - 3abc = (a + b + c)(a^{2} + b^{2} + c^{2} - ab - bc - ca) or a 3 + b 3 + c 3 = ( a + b + c ) ( a 2 + b 2 + c 2 a b b c c a ) + 3 a b c a^{3} + b^{3} + c^{3} = (a + b + c)(a^{2} + b^{2} + c^{2} - ab - bc - ca) + 3abc (1) (try to prove it yourself, or there is a proof at the end of this solution). b c a 2 + a c b 2 + a b c 2 = a b c a 3 + a b c b 3 + a b c c 3 = a b c ( 1 a 3 + 1 b 3 + 1 c 3 ) = a b c [ ( 1 a + 1 b + 1 c ) ( 1 a 2 + 1 b 2 + 1 c 2 1 a b 1 b c 1 c a ) + 3 1 a 1 b 1 c ] = a b c 3 a b c = 3 \frac{bc}{a^{2}} + \frac{ac}{b^{2}} + \frac{ab}{c^{2}} \\ = \frac{abc}{a^{3}} + \frac{abc}{b^{3}} + \frac{abc}{c^{3}} \\ =abc\left ( \frac{1}{a^{3}} + \frac{1}{b^{3}} + \frac{1}{c^{3}} \right ) \\ =abc\left [ \left ( \frac{1}{a} + \frac{1}{b} + \frac{1}{c} \right ) \left ( \frac{1}{a^{2}} + \frac{1}{b^{2}} + \frac{1}{c^{2}} - \frac{1}{ab} - \frac{1}{bc} - \frac{1}{ca} \right ) + 3\cdot \frac{1}{a}\cdot \frac{1}{b}\cdot \frac{1}{c} \right ] \\ =abc\cdot \frac{3}{abc} \\ =3 2. From 1 a + 1 b + 1 c = 0 \frac{1}{a} + \frac{1}{b} + \frac{1}{c} = 0 , we got that: 1 a + 1 b = 1 c ( 1 a + 1 b ) 3 = 1 c 3 \frac{1}{a} + \frac{1}{b} = -\frac{1}{c} \\ \left ( \frac{1}{a} + \frac{1}{b} \right)^{3} = -\frac{1}{c^{3}} Now, we have another fact that a 3 + b 3 = ( a + b ) 3 3 a b ( a + b ) a^{3} + b^{3}=(a + b)^{3} - 3ab(a+b) , you can prove this by expanding ( a + b ) 3 (a+b)^{3} . Thus: b c a 2 + a c b 2 + a b c 2 = a b c ( 1 a 3 + 1 b 3 + 1 c 3 ) = a b c [ ( 1 a + 1 b ) 3 3 1 a b ( 1 a + 1 b ) + 1 c 3 ] = a b c [ 1 c 3 3 a b ( 1 c ) + 1 c 3 ] = a b c 3 a b c = 3 \frac{bc}{a^{2}} + \frac{ac}{b^{2}} + \frac{ab}{c^{2}} \\ =abc\left ( \frac{1}{a^{3}} + \frac{1}{b^{3}} + \frac{1}{c^{3}} \right ) \\ =abc\left [ \left ( \frac{1}{a} + \frac{1}{b} \right )^{3} - 3\frac{1}{ab}\left ( \frac{1}{a} + \frac{1}{b} \right ) + \frac{1}{c^{3}}\right ] \\ =abc\left [ -\frac{1}{c^{3}} - \frac{3}{ab}\left ( -\frac{1}{c} \right ) + \frac{1}{c^{3}} \right ] \\ =abc\cdot \frac{3}{abc} \\ =3 Proof of (1): You may prove that a 3 + b 3 = ( a + b ) 3 3 a b ( a + b ) a^{3} + b^{3}=(a + b)^{3} - 3ab(a+b) . Using this, we have: a 3 + b 3 + c 3 3 a b c = ( a + b ) 3 3 a b ( a + b ) + c 3 3 a b c = ( a + b ) 3 + c 3 3 a b ( a + b ) 3 a b c = ( a + b + c ) [ ( a + b ) 2 ( a + b ) c + c 2 ] 3 a b ( a + b + c ) = ( a + b + c ) ( a 2 + 2 a b + b 2 a c b c + c 3 3 a b ) = ( a + b + c ) ( a 2 + b 2 + c 2 a b b c c a ) a^{3}+b^{3}+c^{3}-3abc \\ =(a+b)^{3}-3ab(a+b)+c^{3}-3abc \\ =(a+b)^{3}+c^{3}-3ab(a+b)-3abc \\ =(a+b+c)[(a+b)^{2}-(a+b)c+c^{2}]-3ab(a+b+c) \\ =(a+b+c)(a^{2}+2ab+b^{2}-ac-bc+c^{3}-3ab) \\ =(a+b+c)(a^{2}+b^{2}+c^{2}-ab-bc-ca)

Rajen Kapur
Jul 22, 2016

Let a, b and c be the roots of x 3 S x 2 a b c = 0 x^3 - Sx^2 - abc=0 , the coefficient of x x is zero (the sum of reciprocals being 0). Dividing this by x 3 x^3 we get the equation, 1 S x a b c x 3 = 0 1 - \frac{S}{x} - \frac {abc}{x^3}=0 . As the expression to be evaluated can be re-written as a b c ( 1 a 3 + 1 b 3 + 1 c 3 ) abc(\frac{1}{a^3}+\frac {1}{b^3} + \frac {1}{c^3}) , after putting x=a, then x=b, then x=c in the equation succesively and adding them gives 3 S ( 1 a + 1 b + 1 c ) a b c ( 1 a 3 + 1 b 3 + 1 c 3 ) = 0 3 - S(\frac {1}{a} + \frac{1}{b} + \frac{1}{c}) - abc(\frac {1}{a^3} + \frac {1}{b^3} + \frac {1}{c^3})=0 , where multiplier of S is 0 (given), we find the value of the required expression as 3. ANSWER

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...